Phospholipid Scramblase 1 Potentiates the Antiviral Activity of Interferon - Dong, Beihua (American Society for Microbiology, 2004)
Phospholipid scramblase 1 (PLSCR1) is an interferon (IFN)- and growth factor-inducible, calcium-binding protein that either inserts into the plasma membrane or binds DNA in the nucleus depending on its state of palmyitoylation. In certain hematopoietic cells, PLSCR1 is required for normal maturation and terminal differentiation from progenitor cells as regulated by select growth factors, where it promotes recruitment and activation of Src kinases. PLSCR1 is a substrate of Src (and Abl) kinases, and transcription of the PLSCR1 gene is regulated by the same growth factor receptor pathways in which PLSCR1 potentiates afferent signaling. The marked transcriptional upregulation of PLSCR1 by IFNs led us to explore whether PLSCR1 plays an analogous role in cellular responses to IFN, with specific focus on antiviral activities. Accordingly, human cells in which PLSCR1 expression was decreased with short interfering RNA were rendered relatively insensitive to the antiviral activity of IFNs, resulting in higher titers of vesicular stomatitis virus (VSV) and encephalomyocarditis virus. Similarly, VSV replicated to higher titers in mouse PLSCR1(−/−) embryonic fibroblasts than in identical cells transduced to express PLSCR1. PLSCR1 inhibited accumulation of primary VSV transcripts, similar to the effects of IFN against VSV. The antiviral effect of PLSCR1 correlated with increased expression of a subset of IFN-stimulated genes (ISGs), including ISG15, ISG54, p56, and guanylate binding proteins. Our results suggest that PLSCR1, which is itself an ISG-encoded protein, provides a mechanism for amplifying and enhancing the IFN response through increased expression of a select subset of potent antiviral genes.